2007
DOI: 10.1177/0959680107081745
|View full text |Cite
|
Sign up to set email alerts
|

Company-level Strategies for Raising Basic Skills: A Comparison of Corus Netherlands and UK

Abstract: ■ This article reports findings from a study of the factors that shape workplace training practices and influence workers' participation. A comparison of basic skills training in steel production facilities in the Netherlands and the UK reveals that institutional frameworks matter but also that management attitudes and union activities influence training arrangements and set conditions for participation. Participation in training depends on these conditions as well as on personal characteristics of workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…The majority of the studies (n = 14) found that organizational support related positively to participation in development activities (Hurtz & Williams, 2009;Leisink & Greenwood, 2007;Maurer et al, 2003). A similar relation was found for social support (Garavan et al, 2010;Maurer et al, 2002;Noe & Wilk, 1993) and supervisor support (Chan & Auster, 2003;Ito & Brotheridge, 2005;Leisink & Greenwood, 2007;Maurer & Tarulli, 1994;Murray & Lawry, 2011;Noe, 1996;Tharenou, 2001;Warr & Birdi, 1998). Warr and Birdi (1998) also confirmed this positive relationship for support from colleagues; however, Maurer and Tarulli (1994) found a negative relationship regarding this support, whereas social integration with colleagues was statistically nonsignificant (Doornbos et al, 2008).…”
Section: Antecedents Of Employees' Participation In Work-related Learsupporting
confidence: 75%
See 1 more Smart Citation
“…The majority of the studies (n = 14) found that organizational support related positively to participation in development activities (Hurtz & Williams, 2009;Leisink & Greenwood, 2007;Maurer et al, 2003). A similar relation was found for social support (Garavan et al, 2010;Maurer et al, 2002;Noe & Wilk, 1993) and supervisor support (Chan & Auster, 2003;Ito & Brotheridge, 2005;Leisink & Greenwood, 2007;Maurer & Tarulli, 1994;Murray & Lawry, 2011;Noe, 1996;Tharenou, 2001;Warr & Birdi, 1998). Warr and Birdi (1998) also confirmed this positive relationship for support from colleagues; however, Maurer and Tarulli (1994) found a negative relationship regarding this support, whereas social integration with colleagues was statistically nonsignificant (Doornbos et al, 2008).…”
Section: Antecedents Of Employees' Participation In Work-related Learsupporting
confidence: 75%
“…As mentioned, Harris found that the effect of being a union member was stronger in larger firms. In line with this result, Booth found a positive effect of union coverage within an organization, whereas Leisink and Greenwood (2007) argued that union activities can play an important role in training arrangements for low-skilled employees.…”
Section: Antecedents Of Employees' Participation In Work-related Learsupporting
confidence: 59%
“…The age profile in the industry -with the majority of those employed over 45 -seems to make this particularly difficult. Employers are seeking new forms of work-based training and learning if there is to be a real chance of continued production with the current workforce (Leisink and Greenwood, 2007 ;Stroud and Fairbrother, 2005 ). Given these tremendous changes for workers, we will now analyse the reactions of labour to the ongoing restructuring and downsizing of the industry.…”
Section: The Fall Of Communismmentioning
confidence: 97%
“…This perspective is too pessimistic, however, at least when it comes to Germany). It is true that in the realm of workplace training there is a need of widespread initiatives (see Leisink and Greenwood, 2007 ), but unions have been very successful in negotiating training after redundancy. Cooperative approaches have been very promising in this area, particularly in the establishment of so-called transfer agencies, directed at lessening the effects of corporate downsizing.…”
Section: Trade Unions and Restructuringmentioning
confidence: 98%
See 1 more Smart Citation